Biochemical Defense Arsenal, Genes/QTLs and Transcripts for Imparting Anthracnose Resistance in Common bean (Phaseolus vulgaris L.) - Safoora Shafi; Mohd Tahir; Vanya Bawa; Farkhandah Jan; Neeraj Choudhary; Mohd Anwar Khan; Yogita Singh; Upendra Kumar; Bilal Ahmad Bhat; Waseem Ahmad Dar; Parvaze Ahmad Sofi; Mohd. Ashraf Bhat; et al. (Plant Stress)
Anthracnose (ANT), caused by Colletotrichum lindemuthianum, is the most devastating disease affecting common bean (Phaseolus vulgaris L.), leading to significant yield losses in the Western Himalayas. The study provides a comprehensive understanding of ANT resistance via trait phenotyping, biochemical profiling, genome-wide association studies (GWASs), and RNA sequencing. The assessment of bean association mapping panel in different environments revealed a diverse spectrum of resistance levels. Biochemical analysis revealed distinctive defense responses against ANT infection among different genotypes. GWAS approach identified 24 significant marker‒trait associations (MTAs) distributed across all 11 bean chromosomes. Notably, 03 MTAs (BMr205, BMr269 and BMr244) present on chromosome Pv07 were validated for ANT, and the remaining MTAs were novel MTAs for ANT. Transcriptome sequencing of resistant (PBG-3) and susceptible (PBG-26) genotypes under mock and 120-hour post inoculation conditions revealed key differentially expressed genes, such as leucine-rich repeat domain-containing protein (PHAVU_007G087700g), NB-ARC domain-containing protein (PHAVU_003G002500g) and transcription factors pivotal for disease resistance. The expression patterns of four genes (PHAVU_007G087700g, PHAVU_003G002500g, PHAVU_007G056100g and PHAVU_003G003000g) were validated through quantitative reverse transcription polymerase chain reaction (qRT‒PCR). Furthermore, the integration of GWAS-identified candidate genes with transcriptomics and cross-referencing with previous studies validated overlapping regions and common candidate genes, enriching our understanding of the genetic basis of ANT resistance. Therefore, the results offer a holistic perspective on ANT resistance in common bean, providing a foundation for targeted breeding efforts. The identified potential candidate genes and associated pathways will contribute valuable insights into the development of ANT resistant common bean varieties.